2022
DOI: 10.1177/00405175221114931
|View full text |Cite
|
Sign up to set email alerts
|

Nano TiO2/amino-benzotriazole functionalization of cotton knitted fabrics for ultraviolet protection and antibacteria by pad-dry method

Abstract: In this work, multifunctional knitted fabrics with ultraviolet resistance and antibacterial properties are presented. The functional coating was fabricated on cotton fabric through a facile one step pad-dry process after being dipped in benzotriazole derivative and titanium dioxide mixture solution. Alkali catalyzed polymerization was applied to synthesis amino-benzotriazole, which could form covalent bonds with cellulose after fixation on cotton fiber. The coating was compacted and agglutinated to the cotton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Moreover, in comparison with the exhaustion method, the air permeability of the facemask comprising dip-pad-dry was substantially lower (## p < 0.01). This was expected, in what concerns change induced by the electrospinning [5,7], dip-pad-dry [75,76] and exhaustion [77] functionalisation methods. Consequently, more opportunities are created for harmful particle collision with the fibrous structures following their contact with the multilayer [5].…”
Section: Air Permeabilitymentioning
confidence: 80%
“…Moreover, in comparison with the exhaustion method, the air permeability of the facemask comprising dip-pad-dry was substantially lower (## p < 0.01). This was expected, in what concerns change induced by the electrospinning [5,7], dip-pad-dry [75,76] and exhaustion [77] functionalisation methods. Consequently, more opportunities are created for harmful particle collision with the fibrous structures following their contact with the multilayer [5].…”
Section: Air Permeabilitymentioning
confidence: 80%
“…This work was compared with the existing research on TiO 2 -based antibacterial and antiultraviolet cotton fabrics, and the information on each research is shown in Table . Shao et al functionalized cotton fabrics with nano TiO 2 /amino-benzotriazole, resulting in a UV protection coefficient of 146.2 and bacterial inhibition rates of 86.40% against E. coli and 83.34% against S.…”
Section: Resultsmentioning
confidence: 99%
“…This work was compared with the existing research on TiO 2based antibacterial and antiultraviolet cotton fabrics, and the information on each research is shown in Table 2. Shao et al 36 functionalized cotton fabrics with nano TiO 2 /amino-benzotriazole, resulting in a UV protection coefficient of 146.2 and bacterial inhibition rates of 86.40% against E. coli and 83.34% against S. aureus. Li et al 5 deposited varying concentrations of TiO 2 nanoparticles on cotton fabrics and subsequently grew Ag nanoparticles on TiO 2 through a chemical reduction method.…”
Section: Antibacterial Properties Of Scsb-simentioning
confidence: 99%